Traduttore Traditore: How the “Unfaithful” Illuminate Translation and Interpreting Studies - Miletich, Marko (Estudios de Traducción, 2026)
This article examines deviant practices found in fictional portrayals of translators and interpreters. The diverse manifestations of misconduct shown here serve to illuminate the moral complexities inherent in linguistic mediation, revealing a typology of professional misconduct that ranges from textual appropriation, in which translators systematically diminish source material through selective omission, to complete textual substitution, wherein practitioners replace entire works with original compositions while maintaining the pretense of translation. Additional categories include gradual authorial usurpation through excessive annotation, deliberate misinterpretation in life-threatening situations, competitive manipulation of interpretive accuracy for personal gain, fabrication of source texts to claim dual authorship, and vindictive narrative modification targeting specific characters. These fictional portrayals serve as critical examinations of the power dynamics embedded in translation and interpretation practice, highlighting tensions between fidelity, creativity, personal ethics, and professional responsibility. The findings demonstrate how literary fiction functions as a site for exploring the boundaries of professional conduct in translation studies, revealing the complex negotiations between accuracy and adaptation, neutrality and intervention, and service and self-interest that characterize the translator/interpreter’s role as cultural intermediary. This typology contributes to understanding the ethical frameworks governing translation and interpretation while illustrating how fictional narratives can illuminate real-world professional dilemmas in cross-linguistic communication.